Implementasi Prinsip Mempersulit Perceraian dalam Undang-Undang Perkawinan : Studi Kasus di Pengadilan Agama Kota Semarang - Asfita Marina Palupi; Dian Septiandani; Efi Yulistyowati (Asosiasi Pengajar dan Peneliti Hukum Ekonomi Islam Indonesia (APPHEISI), 2021)
Law Number 16 Year 2019 adheres to the principle of “complicate divorce”. Thus, the researcher conducted a research in Religious Court of Semarang City, Central Java, focusing on the implementation of the principle to complicate divorce based on Law Number 16 Year 2019 concerning Marriage, the obstacle faced in implementing the principle to complicate divorce under Law Number 16 of 2019 and how to solve the obstacle. This is a is sociological juridical research as this study will discuss the implementation of the principle to complicate divorce as adhered in Law Number 16 of 2019 on Marriage, the obstacles in implementing the principle and how to overcome the problems. Moreover, the specification of this study is qualitative one conducted by a field research and a library research. The method usedincludes primary dataand supported data secondary. The method of data analysis used in this study is a qualitative one and the approach used is statute approach.The results of the study indicate that has implemented the principle of “complicate divorce” as mandated in the general explanation of Law Number 16 of 2019 on Marriage since a divorce claim to be filed before a Religious court must be based on valid reasons and the reason must able to be proven based on Article 19 Government Regulation Number 9 Year 1975. The obstacles found in the implementation of the principle “complicate divorce” in are a strong willingness from the parties or one of the parties to divorce which makes the judge difficult to strive for peace to the parties, the absence of the divorce defendant on the set trial day makes the mediation efforts cannot be carried out, and a limited time possessed by the panel of judges in resolving and reconciling the divorce litigating parties. The solutions for these problems are the support of the judges and providing a special room for mediation. Keywords: Implementation, Principles of “Complicate Divorce”, Law Number 16 Year 2019, Religious Court of Semarang City. Abstrak Undang-undang Nomor 16 Tahun 2019 tentang perkawinan menganut prinsip “mempersulit perceraian“. Sehubungan dengan hal tersebut, peneliti ingin melakukan penelitian di Pengadilan Agama Kota Semarang dalam mengimplementasikan prinsip mempersulit perceraian berdasarkan UU Perkawinan. Tipe/jenis penelitian ini adalah yuridis sosiologis Spesifikasi penelitian adalah penelitian lapangan (field research) dan penelitian kepustakaan (library research). Metode yang digunakan meliputi data primer dan didukung data sekuder. Metode analisis data yang dipakai dalam penelitian ini analisis kualitatif. Hasil penelitian menunjukkan bahwa telah mengimplementasikan prinsip mempersulit perceraian sebagaimana diamanatkan dalam penjelasan umum UU Perkawinan, karena suatu gugatan perceraian atau talak untuk diajukan di muka sidang pengadilan Agama harus disertai alasan-alasan yang sah dan alasan tersebut harus dapat dibuktikan sesuai dengan Pasal 19 PP No. 9 Tahun 1975. Kendala yang dihadapi dalam pelaksanaan prinsip mempersulit terjadinya perceraian di Pengadilan Agama Semarang adalah kemauan keras dari para pihak atau salah satu pihak untuk tetap bercerai. Upaya mengatasinya adalah adanya dukungan para hakim, dan ada ruangan khusus untuk mediasi. Kata Kunci: Implementasi, Prinsip, Mempersulit Perceraian, UU No. 16 tahun 2019, PA Semarang.